PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DAN KUALITAS LAYANAN - Ni Made Dwi Puspitawati; I Gede Riana (Faculty of Economics and Business Udayana University, 2014)
The expectancy theory argues that the actions of employees were motivated by the hope that the employee will obtained some result, the optimal service quality is achieved when employees are satisfied and commited with their work. The study aims is to determine the effect of job satisfaction to organizational commitment and service quality of Bali Hyatt Sanur Hotel employee. The population were all employees which directly deals with consumers, 166 samples were chosen by proportional random sampling technique. Data were collected using a questionnaire and analysed using path analysis with SPSS. The results showed that job satisfaction has a positive effect on organizational commitment and service quality, on the other side, organizational commitment has a positive effect on the service quality. The implications of this study showed that the match between workload and salary is very important to maintain employee organizational commitment. Job satisfaction will increase employee loyalty and the willingness to provide the best service quality